Effects of dance sports exercise on vestibular function and balance of children with sensorineural hearing loss; a randomized quasi-experimental trial - Hu, Fang; Qiu, Xuan; Wu, Xinbo; Wu, Xilong; Li, Han; Kim, Sukwon (Frontiers in Pediatrics, 2024)
Background Sensorineural hearing loss (SNHL) children have difficulty living and limited movement due to impaired vestibular function and reduced balance ability. Objectives The present study evaluated the effects of Latin dance training on the vestibular function and balance of SNHL children. Methods Thirty SNHL children with no difference in vestibular function and balance ability were randomly divided into two groups, the Latin dance training group (LTG, n = 15) and the control group (CONG, n = 15). Vestibular function, timed eyes-closed static (ECS) and functional reach test (FRT) were measured before and after the intervention, and a two-way repeated-measures analysis of variance was performed. Results After training, the vestibular function performance of LTG was higher than that of CONG (CONG: 16.425 ± 3.616 vs. LTG: 12.241 ± 2.610, p = 0.0411, ES = 1.3914), the left foot ECS performance of LTG was higher than that of CONG (CONG: 2.765 ± 0.872 vs. LTG: 4.688 ± 1.113, p = 0.0026, ES = 1.9857), the right foot ECS performance of LTG was higher than that of CONG (CONG: 3.113 ± 0.639 vs. LTG: 4.797 ± 1.071, p = 0.0137, ES = 2.01), the FRT performance of LTG was higher than that of CONG (CONG: 32.009 ± 6.134 vs. LTG: 43.797 ± 6.616, p = 0.0021, ES = 1.9135). Conclusions After Latin dance training, SNHL children improved vestibular function and balance. The static balance ability of the left foot has been improved significantly than right foot.